Surfing and health in the Covid-19 era: a narrative review - McParland, A.; Thijssen, E.; Morris, S.; Straatman, J.; Markovic, O.; Hjortdal, V.; Berg, I.; van de Schoot, D. (Surfing Medicine, 2021)
Surfing is an increasingly popular sport, with an estimated 37 million participants worldwide—a figure likely to rise following surfing`s appearance at the rescheduled Tokyo 2020 Olympics. The COVID-19 pandemic has and has had an impact on the global surfing community and there is a need for guidelines for safe return for both elite and recreational surfers. Generally, surfing has a low-risk injury profile compared to other sports; however, the risk of drowning and adverse events in the water is ever-present. This risk may be heightened in patients with underlying or recent COVID-19 infection. This narrative review aims to summarise the available scientific evidence on surfing and COVID-19, to help both elite and recreational surfers, surfing organisations, and healthcare professionals consider a safe return to surfing during this pandemic.